Adaptions and perceptions on histology and embryology teaching practice in China during the Covid-19 pandemic - Xin Cheng; Lap Ki Chan; Hongmei Cai; Deshan Zhou; Xuesong Yang (Elsevier, 2021)
Backgroud: Under the circumstance of school closures caused by the coronavirus outbreak, medical schools in China began implementing online teaching, including histology and embryology (HE) beginning in the middle of February 2020. The changes in HE education in responding to the pandemic in China needs to be determined, for further adaption of online teaching delivery or blended learning. Methods: A nationwide survey of the major medical colleges was conducted via WeChat. Results: In total, 83 medical schools (one respondent per school) were invited to survey, 78 medical schools responded which represented most medical schools across all the provinces in mainland China, as well as Hong Kong and Macao. The results revealed that 77% (n = 60) and 58% (n = 45) of the responding schools had conducted HE theoretical and practical online teaching, respectively, prior to the pandemic; however, 27% (n = 21) of the medical schools had temporally suspended practical sessions at the time the survey was completed. During the pandemic, 73% (n = 57) and 29% (n = 23) of the medical schools delivered HE theoretical and practical sessions by synchronous live broadcasting, respectively; 65% (n = 51) of the medical schools increased virtual microscopy using during practical sessions. During the pandemic, 54% (n = 42) of the medical schools implemented teaching activities promoting active learning; meanwhile, online assessment was implemented in 84% (n = 66) of the responding medical schools. With regard to the satisfaction with the effectiveness of online teaching during the pandemic, 64% (n = 50) of the medical schools gave positive answers and considered that it was a good opportunity to develop novel and diversified teaching methods. Despite various difficulties such as work overload and unstable online teaching environments, most medical schools are willing to continue or increase theoretical online teaching after the pandemic. Conclusions: Medical institutes in China were the earliest of closing campuses and having complete online teaching experience during the pandemic. This paper presents overall HE teaching situation extracted from the survey, to assist other medical schools optimizing the transitions to quality online teaching within a short time, and to serve as reference for schools that demand essential knowledge in online teaching methods, infrastructure construction, and platform integrations.